Analisis Kualitas Sumber Air Minum (Air Sumur) Masyarakat di Kecamatan Kota Raja Kota Kupang Berdasarkan Jumlah Bakteri Escherichia coli - Agusanaterny, Agusanaterny; Fahira, Seprianus (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
Water is an essential material in life. There is not a living being in this world that does not need and does not contain water. Living cells, both plant and animal, are mostly composed of water, such as in plant cells containing more than 75% or in animal cells containing more than 67%. Research has been carried out on “Analysis of the quality of drinking water sources (well water) for the people of Kota Raja District, Kupang City based on the number of Escherichia coli bacteria. In Kota Raja District, Kupang City, there are 8 villages, namely: Airnona Village, Bakunase Village, Bakunase II Village, Fontein Village, Kuanino Village, Naikoten I Village, Naikoten II Village, and Nunleu Village. Escherichia coli bacteria were used as well water quality parameters. This study aims to determine the quality of drinking water sources based on PERMENKES RI No. 907 of 2002. Water samples were taken from community wells in 8 sub-districts of Kota Raja District, Kupang City. Based on the results of observations using a pH meter, it shows that the well water in the 8 sub-districts has a pH of 7 and 7 where Escherichia coli bacteria live so that the well water in these 8 villages is positive for Escherichia coli bacteria in every 100 ml of well water tested based on this analysis. it can be concluded that the quality of well water in 8 urban villages in Kota Raja Subdistrict, Kupang City in terms of microbiological aspects does not meet the water quality requirements because the wells are not hygienic because the location around the well is used as a place for bathing and washing, adjacent to toilets, sewers and garbage dumps, so the well water can be contaminated with fecal matter.